Effectiveness of Psychotherapy on Suicidal Risk: A Systematic Review of Observational Studies - Méndez-Bustos, Pablo; Calati, Raffaella; Rubio-Ramírez, Francisca; Olié, Emilie; Courtet, Philippe; Lopez-Castroman, Jorge (Frontiers in Psychology, 2019)
Background: Suicidal behavior is a major public health concern worldwide, and the interest in the development of novel and more efficient treatment strategies and therapies to reduce suicidal risk is increasing. Some recent studies have summarized the results of randomized clinical trials (RCTs) assessing the efficacy of psychotherapeutic tools designed to treat patients at suicidal risk. However, observational studies, which reflect real-world effectiveness and may use original approaches, have not been reviewed. Method: The aim of this study is to systematically review the available scientific evidence issued from observational studies on the clinical effectiveness of psychotherapeutic tools designed to treat patients at suicide risk. We have thus performed a systematic search of PubMed and Web of Science databases. Results: Out of 1578 papers, 40 original observational studies fulfilled our selection criteria. The most used psychotherapeutic treatments were dialectical behavioral therapy (DBT, 27.5%) and cognitive behavioral therapy (CBT, 15.0%) in patients with a diagnosis of borderline personality disorder (32.5%) and depression (15.9%). Despite the between-study heterogeneity, interventions lead to a reduction in suicidal outcomes, i.e. suicidal ideation (55.0%) and suicide attempts (37.5%). The content and reporting quality varied considerably between the studies. Conclusion: DBT and CBT are the most widely used psychotherapeutic interventions and show promising results in existing observational studies. Some of the included studies provide innovative approaches. Group therapies and internet-based therapies, which are cost-effective methods, are promising treatments and would need further study.